2021
DOI: 10.7759/cureus.19885
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Sinus Thrombosis in a Patient With Mild Symptoms of COVID-19 Pneumonia

Abstract: Although coronavirus disease 2019 infection is mainly associated with pneumonia, several nonrespiratory complications may also occur. Cerebral venous sinus thrombosis (CVST) is a rare but potentially fatal complication of COVID-19 infection. In order to increase awareness about such life-threatening complications to a large population of patients with otherwise mild COVID-19 infection, we present the clinical course of a 29-year-old unvaccinated female who developed CVST, with eight days of mild COVID-19 infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Fever was the most frequent adverse reaction following the second Sinovac dose, as reported by 262 (32.8%) subjects. Sinovac was tolerated at both dosages, and most side effects were mild and self-limiting [ 19 ]. These findings were similar to those of the above-cited research and indicated that the most commonly reported side effect was fever after receiving the first and second doses, followed by injection site pain and swelling.…”
Section: Discussionmentioning
confidence: 99%
“…Fever was the most frequent adverse reaction following the second Sinovac dose, as reported by 262 (32.8%) subjects. Sinovac was tolerated at both dosages, and most side effects were mild and self-limiting [ 19 ]. These findings were similar to those of the above-cited research and indicated that the most commonly reported side effect was fever after receiving the first and second doses, followed by injection site pain and swelling.…”
Section: Discussionmentioning
confidence: 99%